A flexible, transparent, flame-retardant, regenerated cellulose-based printed electronic substrate

Through the combination of microcrystalline cellulose and nano -magnesium magnesium, to prepare flexible transparent, flame retardant and regenerative cellulose -based printing electronic base, solve the problem of rigidity, opaqueity and environmental pollution of traditional printing circuit boards, and realize low -cost, green environmental protection Printing electronic base.

CN118620249BActive Publication Date: 2025-01-28GUANGDONG YINGTONG PAPER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410623246.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-01-28
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

Traditional printed circuit boards limit their application range due to their rigidity and opacity, and their materials are difficult to degrade naturally, resulting in environmental pollution.

Method used

Micro -crystalline cellulose and nano -magnesium are used to dissolve, regenerate, purify, plasticize, and dryly print electronic bases such as dissolving, regeneration, purification, plasticization, and drying.

Benefits of technology

The prepared printing electron bases are low -cost, light -quality, green degradable, good biocompatibility, good flame retardant performance, etc., and are suitable for flexible printing circuit boards and wearable electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004847729490000071
    Figure BDA0004847729490000071
  • Figure BDA0004847729490000081
    Figure BDA0004847729490000081
Patent Text Reader

Abstract

The present invention relates to the technical field of printed electronic materials, and in particular to a flexible, transparent, flame-retardant regenerated cellulose-based printed electronic substrate. The present invention develops a flexible cellulose-based printed electronic substrate prepared by a regenerated cellulose method, which has excellent transparency, smoothness and flame retardancy, and provides a new idea for the development of green and degradable printed electronic substrates, and has good application value, economic benefits and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of printed electronic materials, and in particular to a flexible, transparent, flame-retardant, regenerated cellulose-based printed electronic substrate. Background Art

[0002] Printed circuit board (PCB) is one of the important components of the electronics industry. From satellites, airplanes and new energy vehicles to smart watches, mobile phones and notebooks, as long as the electronic components of integrated circuits are used, PCB is indispensable. However, the rigidity and opacity of traditional PCBs limit their application scope; on the other hand, since PCBs contain a large amount of metals (gold, silver, copper, zinc, tin, etc.) and non-metals (glass fiber and epoxy resin, etc.) that are difficult to degrade naturally, they bring a heavy burden to the environment every day.

[0003] Microcrystalline cellulose (MCC) is a form of cellulose, usually in the form of cellulose particles or cellulose crystals, with a large surface area and low porosity. Due to its high crystallinity and large crystal size, MCC has higher mechanical strength and thermal stability than other forms of cellulose. MCC is prepared by cellulose pretreatment and post-treatment methods, including acid and alkali treatment of cellulose, mechanical crushing, high temperature treatment, etc. These methods can make the crystal structure of cellulose more orderly and improve the crystallinity and crystal size of cellulose. MCC has been widely used in the fields of pulp, cellulose-based composite materials, nanocellulose membranes, nanocellulose reinforced materials, etc., providing an important technical basis for the development of new materials and the realization of sustainable development.

[0004] In the electronics field, the flame retardancy of materials cannot be ignored, because the materials used in electronic equipment need to be able to withstand fire and high temperatures. The flame retardancy of materials can slow the spread of fire, reduce the risk of fire, and ensure the stability of equipment under extreme conditions. Selecting the right flame retardant to improve the flame retardancy of electronic materials is crucial to ensure the safety of people's lives and property.

[0005] Due to the excellent renewability of cellulose and the fact that it is one of the most abundant resources in nature, printed electronic substrates made of cellulose nanofibers (CNF) have emerged, but due to their complex process and high cost, they have not yet been put into industrial production. Summary of the invention

[0006] The present invention develops a flexible transparent flame-retardant regenerated cellulose-based printed electronic substrate prepared by a regenerated cellulose method, which has excellent transparency, smoothness and flame retardancy. The present invention adopts the following technical scheme to achieve the above, including the steps of:

[0007] (1) adding microcrystalline cellulose to a precooled alkaline urea solution, stirring and dissolving the solution, and obtaining a cellulose mixed solution;

[0008] Then the cellulose mixed solution is centrifuged to remove undissolved fibers to obtain a cellulose solution;

[0009] (2) adding nano-magnesium oxide particles to the cellulose solution, stirring at low temperature until the nano-magnesium oxide and the cellulose solution are mixed, and then placing in a refrigerator to stand and defoam to obtain a nano-magnesium oxide / cellulose composite solution;

[0010] (3) applying the nano-magnesium oxide / cellulose composite solution to a substrate material, and then immersing the substrate material in a regeneration solution to obtain a wet regenerated cellulose film; washing and purifying the wet regenerated cellulose film; after purification, immersing the regenerated cellulose film in a plasticizer for displacement plasticization, and drying to obtain the flexible, transparent, flame-retardant regenerated cellulose-based printed electronic substrate;

[0011] The degree of polymerization of the microcrystalline cellulose in step (1) is 100 to 300.

[0012] The precooling temperature in step (1) is -122 to -15°C.

[0013] The alkaline urea solution described in step (1) is a mixed solution with a ratio of sodium hydroxide / urea / water of 7:12:81 or a mixed solution with a ratio of lithium hydroxide / urea / water of 4.6:15:80.4.

[0014] The violent stirring speed in step (1) is 800 to 1500 rpm, preferably 1000 rpm.

[0015] The stirring time in step (1) is preferably 30±5 min.

[0016] The centrifugation conditions described in step (1) are: 10000 rpm, temperature 10-15°C, time 15-25 min.

[0017] The cellulose solution in step (1) has a cellulose content of 2 to 8%.

[0018] The nano magnesium oxide particle size described in step (2) is 15 nm.

[0019] The substrate material in step (2) is a smooth material that does not react with the nano-magnesium oxide / cellulose composite solution, such as glass, PMMA (organic glass), etc.

[0020] The amount of nano magnesium oxide added in step (2) is 3-9% of the mass of the absolute dry cellulose, preferably 6%.

[0021] The temperature range of the ice water bath in step (2) is 5 to 10°C.

[0022] The regeneration solution described in step (3) is one of distilled water, anhydrous ethanol, a solution of acetone and water in a volume ratio of 2:1, a 5wt% acetic acid solution, a 5wt% sulfuric acid solution and a 5wt% sulfuric acid / sodium sulfate solution, preferably a 5wt% sulfuric acid / sodium sulfate solution.

[0023] The regeneration time described in step (3) is 5-15 minutes.

[0024] The wet membrane purification conditions described in step (3) are 25° C., 32 to 48 hours, during which the water is changed every 8 hours.

[0025] The plasticizer described in step (3) is one of diethyl phthalate ethanol solution, dioctyl terephthalate ethanol solution, tripropionin ethanol solution, triethyl citrate ethanol solution, polyethylene glycol ethanol solution, formamide ethanol solution, and dioctyl adipate ethanol solution, preferably triethyl citrate ethanol solution.

[0026] The plasticizing conditions described in step (3) are: room temperature, plasticizer concentration of 1-20%, and plasticizing time of 1-24 hours, preferably room temperature, plasticizer concentration of 9%, and plasticizing time of 12 hours.

[0027] The drying method described in step (3) is one of natural drying, vacuum hot pressing drying, freeze drying, and drum drying, preferably vacuum hot pressing drying.

[0028] The drying conditions described in step (3) are: vacuum degree -0.9 bar, 60-90° C., 5-10 min, preferably vacuum degree -0.9 bar, 80° C., 6 min.

[0029] A flexible, transparent, flame-retardant, regenerated cellulose-based printed electronic substrate is prepared by any of the methods described above.

[0030] The flexible transparent flame-retardant regenerated cellulose-based printed electronic substrate can be used in the fields of flexible printed circuit boards, flexible electronic materials, solar cell light management layers, RFID anti-counterfeiting packaging, etc.

[0031] The flexible electronic materials include flexible electronic materials used in wearable electronic devices, flexible sensors and flexible display screens.

[0032] The beneficial technical effects of the present invention are embodied in the following aspects:

[0033] (1) The present invention first dissolves microcrystalline cellulose in an alkaline urea system to obtain a transparent cellulose solution, then evenly mixes the cellulose solution with a flame retardant nano-magnesium oxide and then scrapes it onto a glass plate, and then sequentially prepares a flexible, transparent, flame-retardant printed electronic substrate through steps such as regeneration, purification, plasticization, and drying. The substrate has the characteristics of low cost, light weight, green degradability, and good biocompatibility.

[0034] (2) The present invention adopts a simple dissolution regeneration method to prepare the regenerated cellulose membrane. Compared with the cellulose membrane prepared by nanocellulose, the experimental operation is simple and the cost is lower.

[0035] (3) The regenerated cellulose-based printed electronic substrate of the present invention uses microcrystalline cellulose as a raw material. Since microcrystalline cellulose itself has a low degree of polymerization, the cellulose solution concentration that can be prepared is higher than that of raw materials with a high degree of polymerization, such as cotton pulp. The cellulose solution with a higher concentration has better film-forming properties. The prepared film has good strength and integrity, which improves the yield rate and provides the necessary basis for industrial production.

[0036] (4) The regenerated cellulose-based printed electronic substrate of the present invention is compounded with flame retardant nano magnesium oxide, so that its limiting oxygen index value reaches 28% of the flame retardancy, thereby improving its safety during use as a printed electronic substrate.

[0037] (5) The surface of the regenerated cellulose-based printed electronic substrate prepared by the present invention is smooth and flat, which is conducive to reducing the penetration of conductive materials when printing circuits on its surface, thereby avoiding short circuits; in addition, after plasticization with triethyl citrate ethanol solution, although its strength is reduced, its elongation is increased to 4.5 times the original, and its transparency can reach more than 90%, which can be used as a printed electronic substrate with excellent performance. Since the regenerated cellulose film itself has the advantages of low cost, light weight, green degradability, good biocompatibility, etc., the printed electronic substrate prepared by the present invention has potential application prospects in flexible printed circuit boards, especially wearable electronic devices. DETAILED DESCRIPTION

[0038] In order to better understand the present invention, the present invention is further described below in conjunction with specific examples, wherein the terms used in the examples are for describing specific embodiments and do not constitute limitations on the scope of protection of the present invention.

[0039] The microcrystalline cellulose involved in the present invention can be obtained by conventional means, such as commercially available or obtained by acid hydrolysis; the microcrystalline cellulose involved in the examples is purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; the other raw materials used are all commercially available chemically pure or above reagents.

[0040] Example 1

[0041] (1) Preparation of microcrystalline cellulose solution: 7 g of sodium hydroxide and 12 g of urea were accurately weighed on a balance and added to 81 g of distilled water. The mixture was precooled to -12°C in a low-temperature thermostatic bath, and 7 g of absolute dry microcrystalline cellulose (MCC) was added to the solution and stirred vigorously for 30 min (1000 rpm) to obtain a translucent solution. The solution was then centrifuged at 10°C and 10,000 rpm for 20 min to remove undissolved cellulose and obtain a transparent microcrystalline cellulose solution (cellulose content: 6.07%).

[0042] (2) Preparation of nano magnesium oxide / cellulose composite solution: 100 g of the microcrystalline cellulose solution prepared in step (1) was placed in an ice water bath at 10° C., and 0.3642 g of nano magnesium oxide was slowly added while magnetic stirring until the nano magnesium oxide and the cellulose solution were completely mixed. The mixture was then placed in a refrigerator to stand and defoam to obtain a nano magnesium oxide / cellulose composite solution.

[0043] (3) Preparation of regenerated cellulose-based printed electronic substrate: drop the nano-magnesium oxide / cellulose composite solution onto a smooth and clean glass plate, and use a thickness gauge (thickness of 100 μm) to evenly and slowly scrape it from top to bottom. Then, immerse the glass plate in a 5 wt % sulfuric acid / sodium sulfate solution for 5 min to obtain a wet regenerated cellulose film. Transfer the wet film to distilled water and purify it in a water bath oscillator (25° C.) for 32 h to remove residual chemical reagents. During this period, the distilled water was replaced every 8 h. Weigh 36 .4g of anhydrous ethanol is placed in a glass dish, and 3.6g of triethyl citrate (TEC) is added and stirred evenly to obtain a 9wt% triethyl citrate ethanol solution plasticizer, and the purified regenerated cellulose membrane is immersed in the plasticizer at room temperature for displacement plasticization for 12h; finally, the plasticized film is padded in the middle of a polytetrafluoroethylene filter membrane, and two filter papers are added to the outer layer, and the film is placed in a vacuum hot press dryer (-0.9bar, 80°C) and dried for 6min to obtain the flexible, transparent, flame-retardant regenerated cellulose-based printed electronic substrate.

[0044] (4) Performance testing of regenerated cellulose-based printed electronic substrates: Fix the film on the sample stage of the atomic force microscope (AFM) with commercially available double-sided tape, carefully install the probe above the sample, and test the surface roughness of the sample. Fix the sample on the fixture of the UV-visible spectrophotometer (with an integrating sphere) to test the transparency of the sample. Cut the sample into 40*20mm specimens, and use a tensile compression testing machine to test the tensile strength and elongation of the specimens. Use an automatic oxygen index tester to measure the limiting oxygen index value of a 100*20mm specimen to evaluate the flame retardant properties of the sample.

[0045] Example 2

[0046] (1) Preparation of microcrystalline cellulose solution: 4.6 g of lithium hydroxide and 15 g of urea were accurately weighed on a balance and added to 80.4 g of distilled water. The mixture was precooled to -15°C in a low-temperature thermostatic bath, and 7 g of absolute dry microcrystalline cellulose (MCC) was added to the solution and stirred vigorously for 30 min (1000 rpm) to obtain a translucent solution. The solution was then centrifuged at 10°C and 10,000 rpm for 20 min to remove undissolved cellulose and obtain a transparent microcrystalline cellulose solution (cellulose content: 6.07%).

[0047] (2) Preparation of nano-magnesium oxide / cellulose composite solution: 100 g of the cellulose solution prepared in step (1) was placed in an ice water bath at 10° C., and 0.3642 g of nano-magnesium oxide was slowly added while magnetic stirring until the nano-magnesium oxide and the cellulose solution were completely mixed and then placed in a refrigerator to stand and defoam.

[0048] (3) Preparation of regenerated cellulose-based printed electronic substrate: drop the nano-magnesium oxide / cellulose composite solution onto a smooth and neat glass plate, and use a thickness gauge (thickness 100 μm) to evenly and slowly scrape it from top to bottom, then immerse the glass plate in a 5 wt % sulfuric acid / sodium sulfate solution for regeneration for 5 min to obtain a wet regenerated cellulose film, transfer the wet film into distilled water, and use a water bath oscillator (25° C.) to purify for 48 h to remove residual chemical reagents, during which the distilled water is replaced every 8 h; weigh 34 g of anhydrous ethanol into a glass dish, and add 3.6 g of polyethylene glycol (PEG), stir evenly to obtain a 9 wt % polyethylene glycol ethanol solution plasticizer, and immerse the purified regenerated cellulose membrane in the plasticizer at room temperature for displacement plasticization for 12 h; finally, place the plasticized film in the middle of a polytetrafluoroethylene filter membrane, add two filter papers on the outer layer, and place it in a vacuum hot press dryer (-0.9 bar, 80° C.) for drying for 6 min to obtain the flexible, transparent, flame-retardant regenerated cellulose-based printed electronic substrate.

[0049] (4) Performance testing of regenerated cellulose-based printed electronic substrates: Fix the film on the sample stage of the atomic force microscope (AFM) with commercially available double-sided tape, carefully install the probe above the sample, and test the surface roughness of the sample. Fix the sample on the fixture of the UV-visible spectrophotometer (with an integrating sphere) to test the transparency of the sample. Cut the sample into 40*20mm specimens, and use a tensile compression testing machine to test the tensile strength and elongation of the specimens. Use an automatic oxygen index tester to measure the limiting oxygen index value of a 100*20mm specimen to evaluate the flame retardant properties of the sample.

[0050] Comparative Example 1

[0051] (1) Preparation of microcrystalline cellulose solution: 7 g of sodium hydroxide and 12 g of urea were accurately weighed on a balance and added to 81 g of distilled water. The mixture was precooled to -12°C in a low-temperature thermostatic bath, and 7 g of absolute dry microcrystalline cellulose (MCC) was added to the solution and stirred vigorously for 30 min (1000 rpm) to obtain a translucent solution. The solution was then centrifuged at 10°C and 10,000 rpm for 20 min to remove undissolved cellulose and obtain a transparent microcrystalline cellulose solution (cellulose content: 6.07%).

[0052] (2) Preparation of nano-magnesium oxide / cellulose composite solution: 100 g of the cellulose solution prepared in step (1) was placed in an ice water bath at 10° C., and 0.3642 g of nano-magnesium oxide was slowly added while magnetic stirring until the nano-magnesium oxide and the cellulose solution were completely mixed and then placed in a refrigerator to stand and defoam.

[0053] (3) Preparation of regenerated cellulose-based printed electronic substrate: drop the nano-magnesium oxide / cellulose composite solution onto a smooth and neat glass plate, and use a thickness gauge (thickness 100 μm) to evenly and slowly scrape it from top to bottom, then immerse the glass plate in a 5wt% sulfuric acid / sodium sulfate solution for regeneration for 5 minutes to obtain a wet regenerated cellulose membrane, transfer the wet membrane to distilled water, and use a water bath oscillating box (25°C) to purify for 32 hours to remove residual chemical reagents, during which the distilled water is replaced every 8 hours; weigh 40g of anhydrous ethanol in a glass dish, and immerse the purified regenerated cellulose membrane in anhydrous ethanol at room temperature for replacement for 12 hours; finally, pad the film in the middle of a polytetrafluoroethylene filter membrane, add two filter papers on the outer layer, and place it in a vacuum hot press dryer (-0.9 bar, 80°C) for 6 minutes to obtain the transparent flame-retardant regenerated cellulose-based printed electronic substrate.

[0054] (4) Performance testing of regenerated cellulose-based printed electronic substrates: Fix the film on the sample stage of the atomic force microscope (AFM) with commercially available double-sided tape, carefully install the probe above the sample, and test the surface roughness of the sample. Fix the sample on the fixture of the UV-visible spectrophotometer (with an integrating sphere) to test the transparency of the sample. Cut the sample into 40*20mm specimens, and use a tensile compression testing machine to test the tensile strength and elongation of the specimens. Use an automatic oxygen index tester to measure the limiting oxygen index value of a 100*20mm specimen to evaluate the flame retardant properties of the sample.

[0055] Comparative Example 2

[0056] (1) Preparation of microcrystalline cellulose solution: 7 g of sodium hydroxide and 12 g of urea were accurately weighed on a balance and added to 81 g of distilled water. The mixture was precooled to -12°C in a low-temperature thermostatic bath, and 7 g of absolute dry microcrystalline cellulose (MCC) was added to the solution and stirred vigorously for 30 min (1000 rpm) to obtain a translucent solution. The solution was then centrifuged at 10°C and 10,000 rpm for 20 min to remove undissolved cellulose and obtain a transparent microcrystalline cellulose solution (cellulose content: 6.07%).

[0057] (2) Preparation of regenerated cellulose-based printed electronic substrate: drop a microcrystalline cellulose solution onto a smooth and neat glass plate, and use a thickness gauge (thickness 100 μm) to evenly and slowly scrape the solution from top to bottom. Then, immerse the glass plate in a 5 wt % sulfuric acid / sodium sulfate solution at a uniform speed for 5 min to regenerate the solution, thereby obtaining a wet regenerated cellulose film. The wet film is transferred to distilled water and purified in a water bath oscillator (25° C.) for 32 h to remove residual chemical reagents. During this period, the distilled water is replaced every 8 h. 36.4 g of anhydrous ethanol is weighed into a glass dish, and 3.6 g of triethyl citrate (TEC) is added and stirred to obtain a 9 wt % triethyl citrate ethanol solution plasticizer. The purified regenerated cellulose film is immersed in the plasticizer at room temperature for displacement plasticization for 12 h. Finally, the plasticized film is placed in the middle of a polytetrafluoroethylene filter membrane, and two filter papers are added to the outer layer. The film is placed in a vacuum hot press dryer (-0.9 bar, 80° C.) and dried for 6 min to obtain the flexible transparent regenerated cellulose-based printed electronic substrate.

[0058] (3) Performance testing of regenerated cellulose-based printed electronic substrates: Fix the film on the sample stage of the atomic force microscope (AFM) with commercially available double-sided tape, carefully install the probe above the sample, and test the surface roughness of the sample. Fix the sample on the fixture of the UV-visible spectrophotometer (with an integrating sphere) to test the transparency of the sample. Cut the sample into 40*20mm specimens, and use a tensile compression testing machine to test the tensile strength and elongation of the specimens. Use an automatic oxygen index tester to measure the limiting oxygen index value of a 100*20mm specimen to evaluate the flame retardant properties of the sample.

[0059] Effect experiment

[0060] (1) Surface roughness comparison: The arithmetic mean roughness value (Ra) and root mean square roughness value (Rq) measured by atomic force microscopy are used to indicate the smoothness of the film surface; the results are shown in Table 1 below.

[0061] Table 1

[0062]

[0063]

[0064] As a film used as a printed electronic substrate, its surface smoothness is relatively important. If the surface of the substrate is too rough, it may affect the uniformity during the printing process, thereby affecting the performance and reliability of the electronic devices on its surface. The results in Table 1 show that the Ra and Rq values ​​in the embodiment are 16nm and 14nm, respectively, which have relatively good surface roughness; while the surface roughness values ​​of Comparative Example 1, which has not been plasticized, and Comparative Example 2, which has not been flame-retardantly modified with nano-magnesium oxide, are quite different. This may be because some of the nano-magnesium oxide used will agglomerate on the surface of the film, increasing the surface roughness of the film. The addition of plasticizers may help reduce the stress inside the regenerated cellulose film, and the reduction of internal stress can reduce the shrinkage and deformation of the film, making the film surface flatter and slowing down the increase in surface roughness caused by nano-magnesium oxide.

[0065] (2) Comparison of tensile properties, transparency and flame retardant properties: The tensile properties, transparency and flame retardant properties of the films obtained in Examples 1 and 2 were compared with those in Comparative Examples 1 and 2. The results are shown in Table 2:

[0066] The test method is:

[0067] GB 1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles"

[0068] GB / T 2410-2008 Test methods for optical properties of plastic materials

[0069] Vertical ignition method in GB / T 2408-2009 "Test method for combustion performance of plastics - oxygen index method".

[0070] Table 2

[0071] Test Project Tensile strength(MPa) Elongation(%) transparency(%) Limiting oxygen index (%) Example 1 59.3 11.8 90.68 28 Example 2 25.7 19.2 90.56 29 Comparative Example 1 67.9 2.6 83.86 28 Comparative Example 2 58.6 8.2 88.40 18

[0072] Sufficient tensile strength is the basis for the practical application of the film, while good elongation gives the film a certain ductility, ensuring that the film will not break due to brittleness during application in various scenarios. After plasticization with a plasticizer, the tensile strength of the film will decrease. This is because the plasticizer will interfere with the hydrogen bonding of the cellulose molecules and reduce the binding force between the cellulose chains. It can be seen from the table that the tensile strength of the film after plasticization is 12.7% lower than that of Comparative Example 1; but it is worth noting that the elongation of the film after plasticization is increased by 4 to 7 times, and the maximum value can reach 19.2%, which reflects the good flexibility of the regenerated cellulose-based printed electronic substrate provided by the present invention.

[0073] On the other hand, the transparency of Example 1 and Example 2 can reach more than 90%, which shows the great potential of the regenerated cellulose-based printed electronic substrate provided by the present invention in the fields of transparent flexible displays and touch screens.

[0074] The limiting oxygen index method is a test method used to evaluate the flame retardant properties of materials. The limiting oxygen index method is very effective in judging the ease with which polymer materials burn when they come into contact with flames in air. This method measures the minimum oxygen concentration required for a material to maintain its spontaneous combustion state by adjusting the flow rates of oxygen and nitrogen in a combustion furnace. The lower the limiting oxygen index value, the better the material's combustion performance in air, because it only requires a lower oxygen concentration to burn. Conversely, the higher the limiting oxygen index value, the worse the material's combustion performance in air, because a higher oxygen concentration is required to maintain its combustion, that is, the better the flame retardant effect of the material.

[0075] From the limiting oxygen index values ​​of different films in the table, it can be seen that the limiting oxygen index value of the regenerated cellulose-based printed electronic substrate modified with nano-magnesium oxide for flame retardancy is between 28% and 29%, and it is generally believed that materials with a limiting oxygen index value of more than 27% are flame retardant; while the limiting oxygen index value of comparative example 2 without adding nano-magnesium oxide is only 18, which is a flammable material.

[0076] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A method for preparing a flexible, transparent, flame-retardant, regenerated cellulose-based printed electronic substrate, characterized in that: Includes steps: (1) adding microcrystalline cellulose to a precooled alkaline urea solution, stirring to dissolve, and obtaining a cellulose mixed solution; Then the cellulose mixed solution is centrifuged to remove undissolved fibers to obtain a cellulose solution; (2) Add nano-magnesium oxide particles to the cellulose solution, stir at low temperature until the nano-magnesium oxide and the cellulose solution are mixed, and then put into a refrigerator to stand and defoam to obtain a nano-magnesium oxide / cellulose composite solution; (3) applying the nano-magnesium oxide / cellulose composite solution to a substrate material, and then immersing the substrate material in a regeneration solution to obtain a wet regenerated cellulose film; washing and purifying the wet regenerated cellulose film; after purification, immersing the regenerated cellulose film in a plasticizer for displacement plasticization, and drying to obtain the flexible, transparent, flame-retardant regenerated cellulose-based printed electronic substrate; In the step (1), the degree of polymerization of the microcrystalline cellulose is 100 to 300; The plasticizer is one of the following: an ethanol solution of diethyl phthalate, an ethanol solution of dioctyl terephthalate, an ethanol solution of tripropionin, an ethanol solution of triethyl citrate, an ethanol solution of polyethylene glycol, an ethanol solution of formamide, and an ethanol solution of dioctyl adipate; The regeneration solution in step (3) is a 5 wt% sulfuric acid / sodium sulfate solution.

2. The preparation method according to claim 1, characterized in that: The precooling temperature in step (1) is -12°C to -15°C.

3. The preparation method according to claim 1, characterized in that: The alkaline urea solution in step (1) contains: 4.6~7 volume percent of sodium hydroxide or lithium hydroxide; 12~15 volume percent urea.

4. The preparation method according to claim 1, characterized in that: The centrifugal temperature in step (1) is 10°C to 15°C.

5. The preparation method according to claim 1, characterized in that: The content of microcrystalline cellulose in the cellulose solution in step (1) is 2-8 wt %.

6. The preparation method according to claim 1, characterized in that: In the step (2), the amount of nano magnesium oxide added is 3-9% of the mass of the absolute dry microcrystalline cellulose.

7. The preparation method according to claim 1, characterized in that: The temperature range of low temperature stirring in step (2) is 5°C to 10°C.

8. The preparation method according to claim 1, characterized in that: In step (3), the substrate material is immersed in the regeneration solution for 5 min to 15 min.

9. The preparation method according to claim 1, characterized in that: The cleaning and purification conditions in step (3) are to immerse in distilled water and shake for 32-48 hours; and the distilled water is replaced at most every 8 hours.

10. The preparation method according to claim 1, characterized in that: The plasticizing conditions in step (3) are: plasticizer concentration 1-20wt%, and plasticizing time 1-24h.

Citation Information

Patent Citations

  • Method for preparing film for high barrier property packaging by using bacterial cellulose

    CN102391534A

  • Cellulose-based battery diaphragm with flame retardant property and preparation method thereof

    CN116073071A